The development of a guide for nurse leaders in higher education - Pottere, Danita; Tolson, Danita (International Journal of Advanced Nursing Studies, 2017)
Aim: Little is known regarding mentoring and supportive resources to assist, retain, and support nurse administrators at Historically Black Colleges and Universities (HBCUs). The purpose of this paper is to discuss and describe the analysis of nurse leaders expressed journey to leadership, and a provide a guide for nursing leadership development.Methods: Thematic analysis of nurse leaders expressed challenges and terms and concepts of nursing leadership that prepared them for their role as a successful nurse leader.Results: Themes were derived from the analysis of past distinguished nurse leaders and provided a foundation for the development of mentoring guide for African American nurse leaders.Conclusions: Mentoring and supportive resources are essential in retaining nurse leaders in higher education. A guide on how to retain and support nurse administrators at HBCUs. This guide serves as a foundation for colleges and universities in their recruitment, orientation, and retention of nurse administrators in higher education.